2022
DOI: 10.1186/s12913-022-07810-z
|View full text |Cite
|
Sign up to set email alerts
|

Intersectoral collaboration at a decentralized level: information flows in child welfare and healthcare networks

Abstract: Background As needs of families with social and behavioral health problems often exceed the expertise and possibilities of a single professional, service or organization, cross-service collaboration is indispensable to adequately meeting those needs. Despite the progressive focus on organizing integrated care, service fragmentation and service duplication remain persistent problems in child welfare and healthcare service delivery systems. A crucial factor to overcome these problems is informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 50 publications
(64 reference statements)
0
25
0
2
Order By: Relevance
“…Also, an important facilitator for cross-service collaboration is the presence of information exchange relationships within a child service network [6,8,71]. As information exchange is vital for a shared understanding of families' needs, a timely response and inter-professional collaboration, network managers should consider strategies to build and preserve internal stable relationships [43,72]. An important point of concern for network managers is that they cannot effectively play the lead role when the purported lead organization is not identified as such by the network members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, an important facilitator for cross-service collaboration is the presence of information exchange relationships within a child service network [6,8,71]. As information exchange is vital for a shared understanding of families' needs, a timely response and inter-professional collaboration, network managers should consider strategies to build and preserve internal stable relationships [43,72]. An important point of concern for network managers is that they cannot effectively play the lead role when the purported lead organization is not identified as such by the network members.…”
Section: Discussionmentioning
confidence: 99%
“…Here it is also important that the type of relationship, i.e., horizontal or vertical, with the lead organization is considered. It has been shown that the structure of the network depends on the tangibility of resources being exchanged [72][73][74][75][76]. This could mean that organizations in the network that primarily exchange tangible resources with the lead organization, such as financial capital through contracts and invoices, function better with a vertical, buyer-supplier relationship with the lead organization.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships among people and organizations are expressions of power (im)balances, which is a fundamental factor that requires continued research to provide a better understanding of how to achieve shared goals ( Glandon et al, 2019 ; Such et al, 2022 ). A deeper understanding of the diversity of arrangements for the various public services involved in intersectoral actions and the different levels of involvement and integration among the services, policymakers, and practitioners is required ( Blanken et al, 2022 ; Neves et al, 2021 ; Okeyo et al, 2020 ). The mapping of the intersectoral networks within various contexts can contribute to understanding the relationships and ways this network works, identifying patterns of interaction (both formal and informal) to refine the knowledge of types of intersectoral arrangements.…”
Section: Introductionmentioning
confidence: 99%
“…Au Québec (Canada), les récents débats publics relatifs à la maltraitance envers les enfants ont mis en exergue les problématiques internes aux services de protection de l'enfance (ci-après, SPE) et le manque de continuité entre ces services et les services offerts en communauté. Cette problématique est également documentée à l'international (Nouman et al, 2020;Tung et al, 2019;Blanken et al, 2022). Le quotidien de la pratique du personnel infirmier agissant en prévention de la maltraitance reste paradoxalement méconnu et peu documenté.…”
Section: Introductionunclassified